Citizen Vermigli: the political animal in Vermigli's commonwealth. Issue 1 (5th February 2014) - Jenkins, Gary
Abstract : Peter Martyr Vermigli's flight from Italy in 1542 left him divested of his Catholic religious heritage, but the same is not to be asserted for his Florentine republicanism. Vermigli has been viewed either as a republican (Bravi) or inclined to monarchism (Kingdon and Kirby) consonant with his time in England. This essay treats Vermigli's presuppositions on what the human animal is, and what polity best suits such a creature. This essay engages Vermigli the Humanist in light of his Christian anthropology, and in particular his thinking about the ultimate end for humans created in the image and likeness of God, as well as what this likeness tell us about the human ability to reach its telos faced with the reality of the Fall.